2002
DOI: 10.1046/j.1365-3180.2002.00260.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial variability in the degradation rates of isoproturon and chlorotoluron in a clay soil

Abstract: Thirty separate soil samples were taken from different locations at the Brimstone farm experimental site, Oxfordshire, UK. Incubations of isoproturon under standard conditions (15 °C; −33 kPa soil water potential) indicated considerable variation in degradation rate in the soil, with the time to 50% loss (DT50) varying from 6 to 30 days. These differences were confirmed in a second comparative experiment in which degradation rates were assessed in 11 samples of the same soil in two separate laboratories using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
26
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(29 citation statements)
references
References 16 publications
3
26
0
Order By: Relevance
“…There have been previous reports of a nonspecific relationship between high pH and rapid biodegradation of carbamate insecticides (21), dicarboximide fungicides (26), substituted urea herbicides (27,28), and triazine herbicides (12). The important effect of pH was further supported in our studies by the results from the experiments in which the pH of two soils (pH 4.7 and 5.7) was increased by addition of CaCO 3 , and these soils behaved like the original United Kingdom soils with a higher pH.…”
Section: Discussionmentioning
confidence: 99%
“…There have been previous reports of a nonspecific relationship between high pH and rapid biodegradation of carbamate insecticides (21), dicarboximide fungicides (26), substituted urea herbicides (27,28), and triazine herbicides (12). The important effect of pH was further supported in our studies by the results from the experiments in which the pH of two soils (pH 4.7 and 5.7) was increased by addition of CaCO 3 , and these soils behaved like the original United Kingdom soils with a higher pH.…”
Section: Discussionmentioning
confidence: 99%
“…A recent pesticide database (Footprint, 2007; http://www.eu -footprint.org/ppdb.html, accessed April 2010) reports half-life values (days) in soil, derived from laboratory studies at 20°C, of 73.5 for azoxystrobin, 59 for chlorotoluron, and 226 for epoxyconazole. However, a certain variability exists, and in other research half-lives are longer, i.e., more than 2 years (at 10°C) for epoxyconazole (4), 62 to 107 days for azoxystrobin (10), and 30 to 200 days for chlorotoluron (36), showing that significant degradation should be measured on a time scale of months or years (8, 9) according to the results of a recent review on pesticide persistence (3).The use of such persistent pesticides on agricultural fields can have a high impact on the environment through leaching into aquifers and altering the microbial community and processes in the soil. Investigations of structural and functional changes in soil microbial communities have been done using several methods, including the fatty acid profiling method (14,27,29).…”
mentioning
confidence: 99%
“…A recent pesticide database (Footprint, 2007; http://www.eu -footprint.org/ppdb.html, accessed April 2010) reports half-life values (days) in soil, derived from laboratory studies at 20°C, of 73.5 for azoxystrobin, 59 for chlorotoluron, and 226 for epoxyconazole. However, a certain variability exists, and in other research half-lives are longer, i.e., more than 2 years (at 10°C) for epoxyconazole (4), 62 to 107 days for azoxystrobin (10), and 30 to 200 days for chlorotoluron (36), showing that significant degradation should be measured on a time scale of months or years (8,9) according to the results of a recent review on pesticide persistence (3).…”
mentioning
confidence: 99%
“…The phenyl-urea herbicides are of particular significance in this respect, since several members of the group, including isoproturon (IPU) [3-(4-isopropylphenyl)-1,1-dimethylurea] and diuron [3-(3,4-dichlorophenyl)-1,1-dimethylurea] are degraded slowly in soil and are susceptible to leaching. As a result, IPU and diuron are frequently detected as contaminants of agricultural catchments in Europe (23).Studies of the fate of IPU in agricultural fields on contrasting soil types have revealed considerable spatial variability in degradation rates across fields (2,26,27). At two such sites in the United Kingdom, Deep Slade field in Warwickshire and Brimstone farm in Oxfordshire, IPU half-life in soil was found to vary between 6 and 30 days, with degradation rate linked to soil pH.…”
mentioning
confidence: 99%
“…Studies of the fate of IPU in agricultural fields on contrasting soil types have revealed considerable spatial variability in degradation rates across fields (2,26,27). At two such sites in the United Kingdom, Deep Slade field in Warwickshire and Brimstone farm in Oxfordshire, IPU half-life in soil was found to vary between 6 and 30 days, with degradation rate linked to soil pH.…”
mentioning
confidence: 99%